Breasts : the owner's manual : every woman's guide to reducing cancer risk, making treatment choices, and optimizing outcomes - Funk, Kristi (Nashville, Tennessee : W Publishing, 2018)
"A comprehensive guide to total breast health from the go-to breast care expert for Good Morning America and The Doctors. One in eight women will be diagnosed with breast cancer over the course of their lives, and breast cancer is the #1 killer of women ages 20-59. But did you know that only 15 percent of those diagnosed have a single relative with breast cancer? For most of us, family history and genetics do not determine who gets breast cancer--we do! You have power over this disease. In BREASTS: The Owner's Manual, Dr. Kristi Funk shows you how to harness that power. This practical guide equips women with the most up-to-date tools for cancer prevention and outlines a compassionate roadmap for treatment options. Kristi Funk, MD, is a Board-certified breast cancer surgeon based in Los Angeles and co-founder of the Pink Lotus Breast Center, which has transformed the delivery of breast healthcare in America. Long before Dr. Funk performed Angelina Jolie's widely-discussed double prophylactic mastectomy, Dr. Funk strategized with her about the most effective and honest way to communicate her decision to the world. Their announcement led to a permanent increase in preventive testing for the BRCA gene. Now, Dr. Funk takes the broader conversation about total breast health to women everywhere with this straight-talking guide. Her mission is to educate as many women as possible about what they can do to stop breast cancer before it starts. Every year, 1 million cases of breast cancer are diagnosed globally, with more than 240,000 in the US alone. BREASTS: The Owner's Manual will help many women avoid this unwelcome journey and will provide wisdom and practical advice for those already walking this challenging path"--
"Cancer is the #1 killer of women ages 20-59. This holistic guide to total breast health arms women with the most up-to-date tools for prevention and a compassionate and complete guide to treatment options"--
Keywords: Breast -- Care and hygiene; Breast -- Cancer -- Prevention; Breast -- Cancer -- Risk factors; Breast -- Cancer -- Treatment